1988
DOI: 10.1128/mcb.8.1.418
|View full text |Cite
|
Sign up to set email alerts
|

Functional modification of a 21-kilodalton G protein when ADP-ribosylated by exoenzyme C3 of Clostridium botulinum.

Abstract: Exoenzyme C3 from Clostridium botulinum types C and D specifically ADP-ribosylated a 21-kilodalton cellular protein, p21.bot. Guanyl nucleotides protected the substrate against denaturation, which implies that p21.bot is a G protein. When introduced into the interior of cells, purified exoenzyme C3 ADP-ribosylated intracellular p21.bot and changed its function. NIH 3T3, PC12, and other cells rapidly underwent temporary morphological alterations that were in certain respects similar to those seen after microin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
143
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(150 citation statements)
references
References 37 publications
7
143
0
Order By: Relevance
“…al. 1987Rubin et al 1988). The term C3 indicates the third protein toxin beside the C1 neurotoxin and the binary actin-modifying C2 toxin, which are produced by Clostridium botulinum.…”
Section: Introductionmentioning
confidence: 99%
“…al. 1987Rubin et al 1988). The term C3 indicates the third protein toxin beside the C1 neurotoxin and the binary actin-modifying C2 toxin, which are produced by Clostridium botulinum.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ADP-ribosylated p22 was not immunoprecipitated by two other ~21" antibodies, Y13-259 and 6B7 (lanes 4,5). Similarly, the BTx substrate has been reported not to be immunoprecipitated by two polyclonal antibodies raised against p21c-'aS [6,17]. Both the 259 and 6B7 antibodies recognized p21c-"s in "S-labeled 1321Nl cells (lanes 7-9 and not shown), and control experiments demonstrated that ADPribosylation by BTx did not interfere with the immunoprecipitation of ~21'~"" by Y13-259 (lanes 7,8).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of Mg2+ and guanine nucleotides on ADP-ribosylation and the immunological data reported here are consistent with p22 being a Gprotein related to ~21"'. ~21" has been shown to induce differentiation of PC12 cells [24] and Rubin et al [6] recently reported that introduction of purified botulinum exoenzyme C3 into these cells also induced changes in cell morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three members of the rho protein family, A, B and C, are known to occur in human tissues, with more than 90% sequence homology between each other [1,2]. Although the function of the rho proteins is not known, they have been suggested to be involved in regulation of cell proliferation and differentiation, possibly by affecting the cytoskeletal system [3,4]. By analogy with the related ras proteins [5], it is assumed that rho proteins are inactive in the GDP-bound state and active in the GTP-bound form.…”
Section: Introductionmentioning
confidence: 99%